Intervention, Revolution, and Politics in Cuba, 1913-1921 - Perez, Louis A., Jr., 1943- (Book collections on Project MUSE., 1978)
Perez views the various economic, political and diplomatic methods used by the United States government to exert hegemony over Cuba from 1913-1921. He also examines the political turmoil and collapse of the traditional Cuban party structure, as candidates were forced to forge alliances with the U.S.